A Palladium-Catalyzed 4CzIPN-Mediated Decarboxylative Acylation Reaction of O-Methyl Ketoximes with α-Keto Acids under Visible Light - Cheng Wang; Shan Yang; Zhibin Huang; Yingsheng Zhao (Molecules, 2022)
This work presents a palladium-catalyzed oxime ether-directed ortho-selective benzoylation using benzoylformic acid as the acyl source with a palladium catalyst and 4CzIPN as the co-catalyst under light. Various non-symmetric benzophenone derivatives were obtained in moderate to good yields. A preliminary mechanism study revealed that the reaction proceeds through a free radical pathway.